Antecedents and outcomes of flow in Sarawak’s hotel industry with moderating effects of socio-cultural factors - Kasa, Mark Edmund (Universiti Malaysia Sarawak, (UNIMAS), 2015)
As employees have become more educated, independent, and strive to be the best, they have begun to aim for better working life towards improving organizational outcomes. Besides, since most researches related to the hotel industry have concentrated on enhancing the wellbeing of its organization members, this study fits the field of organization development and its application to employees at workplace. This study emphasized on the flow at work and the influence of antecedents (Job characteristic and Burnout), hence the impact on the positive outcome (Organizational Citizenship Behavior) and the negative outcome (Work- Family Conflict). Job characteristic acted as the positive experience, whilst Burnout acted as the negative experience. More specifically, this study utilized moderated mediation approach, whereby socio-cultural factors (Individualism/collectivism) had been assigned as the moderator. The targeted population sample consisted of full-time 3, 4, and 5 star rated hotel employees from various departments in Sarawak, Malaysia. A total of 293 valid responses were obtained, which yielded a final response rate of 58.6%. A 2-stage Structural Equation Modeling (AMOS version 21) technique was used to test the validity of the overall model and the hypothesized relationship between the hypothesized constructs. In addition, this study employed the cross-sectional research design and was conducted within a hotel setting in the Malaysian context. In this study, the mixed-method approach of data analyses was utilized, which was the qualitative method of an in-depth interview, while the quantitative method involved descriptive statistics, Pearson Correlation, and Structural Equation Modeling (SEM). Furthermore, two stages of approaches for the measurement model had been implemented. The result from the Structural Equation Modeling AMOS version 21 indicated that there was a significant relationship between flow and organizational citizenship behavior. None of the antecedents predicted flow while flow did not mediate both antecedents and outcomes. In addition, socio-cultural factor (Individualism) showed a moderating effect in the relationship between flow and organizational citizenship behavior. Understanding these relationships will provide a strategy for hotel employers to attract and to retain or to develop the most capable and talented human capital in the industry. In addition, it will also help hotel employers to facilitate flow experience for greater job satisfaction among the employees towards improving their competitiveness in the hotel business.